+0

If g(x) = 3x^3 - 4x^2 + 5, find g(-2).

0
92
1
+1399

If g(x) = 3x^3 - 4x^2 + 5, find g(-2).

A) -147

B) -35

C) -3

D) 13

E) 45

If f(x) = -x + 4 and g(x) = x^2 - 5, then g(f(-1)) = ?

A) -8

B) 0

C) 4

D) 5

E) 20

If f(x) = x^2 and g(x) = 3x + 1, then f(g(2))= ?

A) 4

B) 7

C) 13

D) 28

E) 49

If f(x) = - 2x^2 + 2x - 3, what is f(5)?

A) -93

B) -43

C) -28

D) -43/5

E) 87

Nov 5, 2019

#1
+190
+2

1. If g(x) = 3x^3 - 4x^2 + 5, find g(-2).

3(-2)^3 - 4(-2)^2 + 5 = 3(-8) - 4(4) + 5 = -24 - 16 + 5 = -35 (B)

2. If f(x) = -x + 4 and g(x) = x^2 - 5, then g(f(-1)) = ?

f(-1) = 1+4 = 5

g(5) = 25 - 5 = 20 (E)

3. If f(x) = x^2 and g(x) = 3x + 1, then f(g(2))= ?

g(2) = 6 + 1 = 7

f(7) = 49 (E)

4. If f(x) = - 2x^2 + 2x - 3, what is f(5)?

f(5) = -2(25) + 10 - 3 = -50 + 10 - 3 = -43 (B)

Nov 5, 2019

#1
+190
+2

1. If g(x) = 3x^3 - 4x^2 + 5, find g(-2).

3(-2)^3 - 4(-2)^2 + 5 = 3(-8) - 4(4) + 5 = -24 - 16 + 5 = -35 (B)

2. If f(x) = -x + 4 and g(x) = x^2 - 5, then g(f(-1)) = ?

f(-1) = 1+4 = 5

g(5) = 25 - 5 = 20 (E)

3. If f(x) = x^2 and g(x) = 3x + 1, then f(g(2))= ?

g(2) = 6 + 1 = 7

f(7) = 49 (E)

4. If f(x) = - 2x^2 + 2x - 3, what is f(5)?

f(5) = -2(25) + 10 - 3 = -50 + 10 - 3 = -43 (B)

Oofrence Nov 5, 2019